2023
DOI: 10.3390/molecules28020858
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoid Content and Profiles of Pumpkin Products and By-Products

Abstract: The goal of this review is to provide an overview of the current findings on the major carotenoids and their content in pumpkin products and by-products. The content of total carotenoids and the composition of carotenoids in pumpkins depend mainly on the species and cultivar, pedoclimatic conditions, the part of the plant (pulp, peel or seed), extraction procedures and the type of solvent used for extraction. The major carotenoids identified in pumpkins were β-carotene, α-carotene, lutein and zeaxanthin. β-Car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 57 publications
1
19
2
Order By: Relevance
“…For all juice samples, only positive values were obtained for the color parameter b* (yellow), the highest values were obtained for apple and pumpkin juice, and it was observed that the addition of preservatives decreases the color intensity. The yellow-orange color of pumpkin is due to the presence of carotenoids [ 101 ] such as α and β-carotene, β-cryptoxanthin, lutein, and zeaxanthin [ 102 , 103 ].…”
Section: Resultsmentioning
confidence: 99%
“…For all juice samples, only positive values were obtained for the color parameter b* (yellow), the highest values were obtained for apple and pumpkin juice, and it was observed that the addition of preservatives decreases the color intensity. The yellow-orange color of pumpkin is due to the presence of carotenoids [ 101 ] such as α and β-carotene, β-cryptoxanthin, lutein, and zeaxanthin [ 102 , 103 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pumpkin fruit is a prevalent food in our daily lives. Edible pumpkin with small fruit is favored by consumers due to its abundant nutrients, such as carotenoids, starch, and polysaccharides. ,, The giant pumpkin AG is often used for viewing due to its attractive appearance quality. Currently, the main focus has been on fruit enlargement in giant pumpkins. , Thus far, the accumulated bioactive metabolites, including flavonoids, coumarins and others, in giant pumpkin fruit have not been thoroughly studied.…”
Section: Discussionmentioning
confidence: 99%
“…Edible pumpkin with small fruit is favored by consumers due to its abundant nutrients, such as carotenoids, starch, and polysaccharides. 14,15,34 The giant pumpkin AG is often used for viewing due to its attractive appearance quality. Currently, the main focus has been on fruit enlargement in giant pumpkins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations